Morphometric Analysis Of Mandibular Foramen In Dry Adult Human Mandibles In North Indian Population And Its Possible Clinical Implication (Journal of Pharmaceutical Negative Results, 2023)
Background: In terms of generating good mandibular nerve blocks and preventing damage to the neurovascular bundles, the mandibular foramen (MF) is an anatomical feature of great relevance in local anesthetic and surgical operations.Objective: This research study aimed to find out the exact position of the mandibular foramen in dry adult human mandibles from North Indian population. Measures were taken between the left and right sides of the mandibles using different landmarks.Method: The location, size, form, and number of mandibular foramen in 125 dry adult human mandibles of undetermined age were noted. All the anatomical parameters were measured using a sliding digital vernier caliper, based on the location of the right and left mandibular foramina from the distinctive landmarks. Continuous data was expressed in mean ± SD while categorical data was measured in median ± IQR. For analyzing any association between study variables, Statistical Package for Social Sciences version 20 was used.Results: In the study mean distance of mandibular foramen (MF) to anterior border of ramus was found to be 16.12mm on the right side and 16.83mm on the left side while the distance of MF from posterior border of ramus was 10.85mm on the right side and 11.26mm on the left side. The width of the ramus (AB-PB) as ascertained by measuring horizontal distance from the anterior border (AB) of the ramus to the posterior border (PB) of the ramus across the foramen was 31.95mm on the left and 31.41mm on the right side. On conducting a paired t-test, a statistically significant difference between the measurement of means on left and right side was found, in parameters of AB-MF and PB-MF while no statistical difference was found in AB-PB.Conclusions: The result indicates significant differences in the location of mandibular foramen. The study showed that the mandibular foramen was located more posterior and at inferior aspect of the mandibular ramus along the vertical and horizontal axis. This study provides useful information for successful local anesthesia during various dental and other surgeries.